ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN MEDIASI PROFITABILITAS - Madhavani, Joceline; Cahyadi, Hadi (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research purposely to examined the effect of capital structure, managerial ownership, and growth on firm value mediated by profitability in food and beverage family companies listed on the Indonesia Stock Exchange in 2019 – 2021. This study used a purposive sampling method, totaling 24 companies and a total sample of 72 data. All data is processed and tested using SmartPLS 4.0.8.4 software. The results of this study prove that capital structure, managerial ownership, and growth have a positive and not significant effect on profitability. Furthermore, capital structure has a significant negative effect on firm value, managerial ownership has a significant positive effect on firm value, while growth has a positive and insignificant effect on firm value. Profitability has a significant effect in a positive direction on firm value. Capital structure, managerial ownership, and growth have a positive and insignificant effect on firm value mediated by profitability.